People: the most important marketing asset of territories - Correia, Ricardo (2020)
Marketing strategies adopted in many territories do not take into consideration the intangible dimension related to local communities, their history, culture and values. By ignoring a driving force of regional identity, such strategies do not value a major source of differentiation. In fact, in a time where the immaterial and relational capital assumes a key role, locals are not only one of the most essential elements for the attractiveness of touristic destinations but also a key for their differentiation when compared to other alternatives. This article puts in evidence the importance of the locals in place branding. It develops a conceptual model where locals emerge as the key element since they are a major source of co-production, co-communication and co-consumption of the regional offer. The model proves to be particularly useful for practitioners, offering relevant insights for managers and policy makers.